Mathematic Reasoning Ability Based on Cognitive Style Field Dependent, Field Intermediate, and Field Independent - Afifah Permana Afifah; Slamet Permana Soro; Ayu faradillah (Jurnal Pendidikan MIPA, 2022)
This study aims to see the effect of 3 types of cognitive styles on students'mathematical reasoning abilities. According to previous research, there has been no research that discusses the 3 types of cognitive styles on mathematical reasoning abilities. The method in this study is a qualitative descriptive approach. The total population of this study was 32 people who sat in SMA class X MIPA A. The selection of subjects in this study was viewed from the top results based on 3 categories of field dependent cognitive style, intermediate field and field independent. So that the main sample is 3 people by representing each category of cognitive style. The selected subjects will be given a follow-up test, namely an interview test related to mathematical reasoning abilities. The results of this study indicate that the intermediate field cognitive style category has higher mathematical reasoning abilities. The conclusion is that the type of student's cognitive style affects the results of mathematical reasoning abilities. Therefore, the teacher's task is to pay more attention to students' mathematical reasoning abilities according to their respective characteristics. Keywords: mathematical reasoning ability, cognitive style, field dependent, field intermediate and field independent DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp880-893